Eksistensi Mabbaca Doang (Studi Pada Kelurahan Benteng Sawitto Kecamatan Paleteang Kabupaten Pinrang) - Hamzah, Erni Irmayanti (Universitas Negeri Makassar, 2018)
The research aimsto discover (i) What is the meaning of Mabbaca Doang to the people in Benteng Sawitto Village of Paleteang Sub-district in Pinrang District? (ii) How is the tradition of Mabbaca Doang as the adhesive of social cohesion to the people in Benteng Sawitto Village of Paleteang Sub-district in Pinrang District? (iii) How is the existence of Mabbaca Doang tradidition in the middle of modernization to the people in Benteng Sawitto Village of Paleteang Sub-district in Pinrang District?. The informants of the research were chosen by using Purposive Sampling technique with the criteria, namely the people of Benteng Sawitto Village, domicile period minimally 10 years, permently settled and ever performed Mabbaca Doang tradition. The research employed qualitative approach, namely the description about a condition objectively. The data were collect through observation, interview, and documentation. The results of the research revel that (i) Mabbaca Doang tradition for the people in Benteng Sawitto Village of Paleteang Sub-district in Pinrang District means as praying to God as thankfulness for the fortune and praying for the family who already passed away as well as Tulabala (Repellent of Misfortune). The ways the people performed are by preparing food, incense, calling Gurru’Katte and inviting guest to pray and eat together, (ii) Mabbaca Doang tradition is as the adhesive of social cohesion. However, there is a difference of social cohesion before and after modernisation, namely the change in the cooperation aspect in preparing Mabbaca Doang, the weaken of direct hospitality among family and community, the interaction only occurred in short time and people tends to attend Mabbaca Doang event if it is profitable for them, (iii) Mabbaca Doang tradition in modern era is still exist. However, there are changes of values in the implementation because of the factors such as education, economy, an religion to the people in Benteng Sawitto Village of Paleteang Sub-district in Pinrang District